Approximation of locally integrable functions on the real line - Stepanets, O.I.; Wang Kunyang; Zhang Xirong (Український математичний журнал, 1999)
We introduce the notion of generalized ψ¯ -derivatives for functions locally integrable on the real axis and investigate problems of approximation of the classes of functions determined by these derivatives with the use of entire functions of exponential type. Вводиться поняті узагальнених ψ¯ -похідних для функцій, локально інтегровних на дійсній осі, і вивчаються задачі наближення класів функцій, що визначаються такими похідними, за допомогою цілих функцій експоненціального типу.